Antibiotic Resistance and Occurrence of Salmonella, E. coli, and S. aureus in Chicken Meat, Kathmandu Valley - Karki, Krisha; Chaudary, Paramanand; Poudel, Sujana; Bastakoti, Pratikshya; Shah, Khul Chandra (Journal of Multidisciplinary Research Advancements, 2026)
This paper examines the prevalence of three significant foodborne illness-causing organisms, Salmonella spp., Escherichia coli, and Staphylococcus aureus, in chicken meat in the Kathmandu Valley and their resistance to widely used antibiotics. Twenty chicken meat samples were collected locally in Kathmandu, Bhaktapur, and Lalitpur. Antibiotic susceptibility was determined by the Kirby-Bauer disc diffusion method. The findings revealed that contamination was widespread: E. coli was found in 40 to 60 per cent of the samples, Salmonella spp. in 30 to 40 per cent, and S. aureus in 20 per cent. Antibiotic susceptibility testing was performed to confirm that nalidixic acid, chloramphenicol, and ciprofloxacin were generally susceptible, whereas ampicillin was highly resistant, as commonly observed in E. coli and S. aureus. More worrying still, more than 50 per cent of S. aureus isolates were MRSA. These findings highlight serious food safety concerns in Nepal’s poultry sector, where poor hygiene during slaughter, processing, and retail handling allows pathogens to persist, and frequent antibiotic use promotes resistance. Improving hygiene practices, regulating antibiotic use in poultry farming and conducting regular microbiological surveillance are critical steps to reduce the risks of foodborne illness and antimicrobial resistance.